CompTIA A+ certification core 1 (220-1101). - Meyers, Mike, 1961- (Packt Publishing, 2022)
This fully revised and updated resource offers complete coverage of the latest release of the CompTIA A+ 220-1101 exam, which is an internationally recognized, fundamental IT training certification. In this course, we will cover all 5 domains as per the latest exam syllabus. Domain 1.0 talks about mobile devices, which cover 15% of the exam. In this domain, we will cover laptop hardware components, mobile device types (tablets, smartphones), and learn how to set up mobile devices. Then, we will cover Domain 2.0, which talks about networking; this domain covers 20% of the questions in the exam. In this domain, we will cover networking hardware devices, learn how to configure a basic SOHO network, learn about networking configuration concepts (IPv4, IPv6, DNS, VPNs), internet connections, and network types (cable, fiber, LANs). Next, Domain 3.0 is about hardware, which covers 25% of the questions in the exam. In this domain, we will cover cables and connectors, motherboards, CPUs, power supplies, RAM, hard drives and SSDs, peripherals, and more. In Domain 4.0, we will cover virtualization and cloud computing, which covers 11% of the questions in the exam. Here, we will cover cloud computing (IaaS, SaaS, PaaS, elasticity, cloud storage) and client-side virtualization (virtual machines, hypervisors). In the final domain, Domain 5.0, we will talk about hardware and network troubleshooting, which covers the largest percent of questions in the exam--29%. Here, we will look at how to resolve problems with best practices and industry standards and how to troubleshoot RAM, motherboards, CPUs, power supplies, hard drives, display issues, mobile device issues, printers, wired/wireless networks. By the end of this course, you will be prepared for the CompTIA A+ Core 1 (220-1101) Certification exam. What You Will Learn Learn all about hardware components Repair and configure mobile devices Set up and configure basic networks Build a PC from the ground up Understand what the cloud is and how virtualization works Troubleshoot hardware and network issues Audience This guide is designed for anyone looking to take and pass the CompTIA A+ Certification Core 1 (220-1101) Certification exam, anyone who wants to improve their skills as a computer or IT technician, or wants to learn awesome stuff about PCs, Macs, mobile devices, networking, the cloud, IT security, and more. A basic familiarity with computers and networks is helpful. Furthermore, CompTIA recommends having 9-12 months of on-the-job experience before taking the A+ exam. This is recommended but not required. About The Authors Mike Meyers: Total Seminars, LLC, is a provider of PC and network repair seminars and certification training services through books, videos, and courseware for thousands of organizations throughout the world including the United Nations, the FBI, and all branches of the US Department of Defense. Mike Meyers is the president and co-founder of Total Seminars, which produces the best-selling CompTIA A+ and Network+ Certification books with over 1 million books in print. He is affectionately called the "Alpha Geek" and is the industry's leading authority on CompTIA Certifications. He has created several other best-selling video courses on CompTIA certifications with the Total Seminars team of instructors. Mike has been involved in the computer and network repair industry since 1987 as a technician, instructor, author, consultant, and speaker. He is the author of numerous popular PC books and videos, including the best-selling CompTIA A+ Certification All-In-One Exam Guide and CompTIA Network+ Certification All-In-One Exam Guide. His humorous and easy-to-follow approach to teaching comes through in his video training courses as well as his classroom instructor-led courses. Making IT concepts easy to understand and fun to learn helps students stay engaged and retain the information. Steve Nicholson: Steve Nicholson is an information security professional with decades of experience in IT. Ever the problem-solver, Steve specializes in digital forensics and incident response, holding an MS in Digital Forensics from UCF, multiple GIAC certifications, and the coveted Lethal Forensicator title. A Marine Corps veteran, Steve volunteers time between both the Marine Corps Cyber Auxiliary and the Civil Air Patrol's CyberPatriot programs and sits on the FLDOE Cybersecurity Curriculum Committee. He is also the NSA program administrator for his college's Center of Academic Excellence in cyber defense. Having taught many students over the years, Steve's favorite part about educating people is the "AHA!" they have when learning something new or perfecting a difficult skill.